Critical Dialogues in Latinx Studies : A Reader - Rúa, Merida M.; Ramos-Zayas, Ana Y. (Book collections on Project MUSE., 2021)
"This book approaches the social histories and contemporary lives of a diverse range of Latina and Latino populations, including immigrants, exiles, refugees, and US-born groups from across the Americas. Adopting a comparative ethnic studies lens that captures local and transnational perspectives on community, national and pan-ethnic identifications, and diverse social and demographic trends, this anthology emphasizes the breadth and dynamism of the ideas, debates, and questions that drive the dynamic field of Latinx Studies. This proposed anthology is unique, not only in its comparative, humanistic social science focus, but also in its structure and organization of key debates, what we call "critical diálogos," in Latinx Studies. The volume deliberately considers each contribution, not exclusively as a stand-alone piece, but as part of a larger disciplinary theme and interdisciplinary conversation. For instance, we highlight the strength of the inter-sectional, comparative, and interdisciplinary Latinx Studies scholarship in our decision to avoid rigid thematic sections (e.g. a section on "gender," or "youth"), in favor of weaving those thematic considerations in relation to broader scholarly discussions (e.g. a section on kinship and forms of relatedness or the world of work). This specific "debate framing" allows readers to identify specific areas of thematic interest, while remaining unavoidably attentive to the diversity and complexity of the everyday lives of Latinx populations, the political economic structures that shape enduring racialization and cultural stereotyping, and the continuing efforts to carve out new lives as diasporic, transnational, global, and colonial subjects"--